Small intestinal starch, dextrin, and glucose digestion in steers - K.K. Kreikmeier; D.L. Harmon; T.B. Avery; Robert T. Brandt Jr. (Kansas Agricultural Experiment Station Research Reports, 1988)
Three Holstein steers (930 lb) were surgically fitted with abomasal and ileal cannulae, portal and mesenteric venous catheters, and an elevated carotid artery and used to study small intestinal starch digestion. Water, corn starch (66 g/hr), corn dextrin (66 g/hr), or glucose (66 g/hr) were continuously infused into the abomasum. Small intestinal disappearance of corn dextrin (57 g/hr) and glucose (57 g/hr) were higher (P<.05) than that of starch (48 g/hr). The percentage of carbohydrate disappearance accounted for as net portal glucose flux was 52, 54, and 72% for corn starch, corn dextrin, and glucose, respectively. Small intestinal starch utilization in the bovine may be limited by starch granular characteristics, enzyme activity, and glucose transport across the small intestine.; Dairy Day, 1988, Kansas State University, Manhattan, KS, 1988;
Keywords: Kansas Agricultural Experiment Station contribution; no. 89-107-S; Dairy; Small intestinal starch; Dextrin; Glucose; Digestion